PEMBENTUKAN KARAKTER SANTRI MELALUI INTERNALISASI NILAI PENDIDIKAN ISLAM DI PESANTREN AL-FATAH MUARA BUNGO JAMBI - Manfaati, Dianah (re-JIEM (Research Journal of Islamic Education Management), 2023)
This study seeks to determine what factors influence the formation of student character at the Al-Fatah Binjai Muara Bungo Jambi Islamic Boarding School, what obstacles teachers face in their efforts to inculcate Islamic religious values, and how teachers instill students with noble morals. Observation, interviews, and documentation are employed as data collection techniques in this qualitative field research. This study found that environmental and family factors are the most influential in shaping the character of Al-Fatah Islamic Boarding School students, whereas the obstacles for teachers in internalizing Islamic religious values are the lack of understanding of the guardians of the boarding school order, the lack of cooperation between the pesantren and parents, the influence of the local environment, and the negative influence of various destructive media. Example, habituation, reprimand and guidance, threats and disciplinary sanctions are the teacher's methods for fostering good character in students.